An examination of the occupational burnout levels of academic staff - Korkmaz, Murat; Yücel, Ali Serdar; Karta, Nurullah (My University, 2015)
In recent years, burnout syndrome has been one of the frequently addressed issues in relation to working life. It can be alleged that burnout is an important issue for the occupation of academics which includes high level of human relations and face-to-face communication. In this respect, this study aimed to determine the occupational burnout levels of academicians and to detect if the burnout levels vary by certain socio-demographic variables (gender, age and educational level). The samples of the study included 830 academic staff members working in private universities located in the provinces of Istanbul, Izmir, Ankara and Bursa. For this purpose, a questionnaire was applied for the determination of participants’ burnout levels. The first part of the questionnaire included questions about the demographic characteristics of the participants while the second part included questions to determine their occupational attitudes. PASW 18.0 software was used for the analysis of the data acquired in the research. Reliability coefficient of the measuring tool (Cronbach Alpha) was found to be 0.924. Descriptive statistics, reliability analysis, ANOVA and Regression Analysis were used within the scope of the analysis. In consequence of the study, it was found that the variables about the participants (age, gender, education) differed in many of the sub-dimensions of the scale that was applied for measuring the burnout level. Furthermore, the regression analysis revealed that increases in the age did not cause occupational burnout in the participants, the participants responded less to the people due to their work, they were not pleased and satisfied with their jobs, and they approached positively to the problems they faced in their jobs. Besides, it was found that as the level of education increased, the participants were exhausted by their jobs, they behaved more harshly towards others, their job satisfied them, and they approached more positively towards problems.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Occupation; Academic; Burnout; Syndrome